Occurrence of Bifidobacteriaceae in human hypochlorhydria stomach - Mattarelli, Paola; Brandi, Giovanni; Calabrese, Carlo; Fornari, Fabio; Prati, Gian Maria; Biavati, Bruno; Sgorbati, Barbara (Journal of aesthetics & culture, 2014)
The human stomach, when healthy, is not a suitable host for microorganisms, but in pathological conditions such as gastritis, when gastric acid secretion is impaired, microbial overgrowth can be observed. Apart from Helicobacter pylori, the composition of microbiota, resident or exogenously introduced during neutral/high pH conditions, has not been investigated thoroughly. Thus, it is possible that Bifidobacteriaceae, important autochthonous and beneficial bacteria of human gastrointestinal microbiota, could over-colonize the stomach of hypochlorhydria patients suffering from autoimmune atrophic gastritis (AAG) or omeprazole-treated (OME) gastritis. This prompted us to characterize the Bifidobacteriaceae in such patients' gastric microbiota and to study its abnormal colonization. Samples of gastric juices, and antrum and corpus mucosa from 23 hypochlorhydria patients (13 AAG and 10 OME) and from 10 control volunteers with base-line normochlorhydria, were cultivated in Brain Heart Infusion (BHI) and selective Bifidobacterium-Tryptone-Phytone-Yeast extract (Bif-TPY) media. The isolates were characterized by the fructose-6-phosphate phosphoketolase (F6PPK) test, electrophoresis of cellular proteins, the fermentation test, guanine-cytosine% DNA content, and DNA-DNA hybridization. Negative F6PPK isolates were characterized by order-specific polymerase chain reaction (PCR). A total of 125 isolates, assigned to the Bifidobacteriaceae family on the basis of their morphology, were obtained from AAG and OME patients, but not from normal subjects. Of these isolates, 55 were assigned to the Bifidobacteriaceae family on the basis of their fructose-6-phosphoketolase (PPK) activity, PPK being the key taxonomic enzyme of this family. The remaining 70 isolates, which were PPK-negative, were attributed to the Actinomycetales order following specific primer PCR analysis. We observed a significantly higher abundance of Bifidobacteriaceae (Bifidobacterium dentium, Scardovia inopinata, and Parascardovia denticolens) in OME group than the AAG group. Furthermore, the Actinomycetales distribution was homogeneous for both hypochlorhydria patient groups. This study suggests that the Bifidobacteriaceae species, typically found in the oral cavity, readily colonizes the hypochlorhydria stomach of OME patients. The clinical relevance and the mechanism underlying this Bifidobacteriaceae presence in OME gastritis requires further functional studies.